2015
DOI: 10.1088/0964-1726/24/8/085034
|View full text |Cite
|
Sign up to set email alerts
|

Study on the thermoelectric properties of PVDF/MWCNT and PVDF/GNP composite foam

Abstract: Always cite the published version, so the author(s) will receive recognition through services that track citation counts, e.g. Scopus. If you need to cite the page number of the author manuscript from TSpace because you cannot access the published version, then cite the TSpace version in addition to the published version using the permanent URI (handle) found on the record page. Abstract. Thermoelectric effect is defined as the revisable translation between thermal and electrical energy. In this paper, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…The TE results for PVDF/CNT composites can be compared with some values from the literature. Sun et al [4] used the same type of PVDF and MWCNTs and the same preparation method for composites, namely melt compounding using a microcompounder DSM15 but with different melt mixing conditions than in our study. The measured S-values with 10 µV/K are slightly lower than in our investigation with 14.3 µV/K.…”
Section: Thermoelectric Properties Of Polymer Composites Filled With mentioning
confidence: 99%
See 1 more Smart Citation
“…The TE results for PVDF/CNT composites can be compared with some values from the literature. Sun et al [4] used the same type of PVDF and MWCNTs and the same preparation method for composites, namely melt compounding using a microcompounder DSM15 but with different melt mixing conditions than in our study. The measured S-values with 10 µV/K are slightly lower than in our investigation with 14.3 µV/K.…”
Section: Thermoelectric Properties Of Polymer Composites Filled With mentioning
confidence: 99%
“…In one of the first studies on the TE performance of melt-processed polymer nanocomposites, Antar et al [3] reported poly(lactic acid) (PLA)/multi-walled CNT (MWCNT)/expanded graphite (EG) materials, in which the highest Seebeck coefficient was 17 µV/K at 32 vol % EG and the highest power factor 9.6 × 10 −2 µW/(m•K 2 ) at 18 vol % MWCNTs. Sun et al [4] reported on poly (vinylidene fluoride) (PVDF) composites filled with MWCNTs or graphite nanoplatelets (GNPs) as solid sample as well as foam. The Seebeck coefficients for solids were found to be 10 µV/K (PVDF/2 or 5 wt % MWCNT) and around 25 µV/K (PVDF/5-15 wt % GNP).…”
Section: Introductionmentioning
confidence: 99%
“…Namely, it can be easily upscaled and it is more environmentally friendly as no solvents are needed. Examples of this new kind of melt-mixed composites are polypropylene (PP) composites filled with single-walled carbon nanotubes (SWCNT) [6][7][8][9][10], polyetherimide/SWCNT nanocomposites [11], polycarbonate/multi-walled carbon nanotube (MWCNT) composites [12][13][14], polylactic acid (PLA)-based composites containing Bi 0.5 Sb 1.5 Te 3 and/or MWCNTs [15], PLA filled with MWCNT and/or expanded graphite [16], and poly(vinylidene fluoride) (PVDF)-based polymer composite foams with MWCNTs or GNPs [17]. In a recent paper, screening of different kinds of CNTs in different polymeric matrices was performed, showing that a variety of TE properties can be achieved when varying CNT and polymer type [18].…”
Section: Introductionmentioning
confidence: 99%
“…The only exception is MWCNT-PDDA/MWCNT-DOC/PEDOT, which exhibits slightly higher PF than that of CNTY/lignin in the present study, due to the high content of PEDOT, and the combination of LbL assembly with electrochemical polymerization to create synergy capable of producing a high power factor. [16] [27] MWCNT/ PVP Mixing 0.6 [28] PEI/MWCNT/ PVP Mixing 1.98 [28] P3HT/MWCNT Mixing 6 [29] WPU/MWCNT/PEDOT:PSS Mixing 1.41 [30] PEDOT:PSS/MWCNT In situ polymerization 2.29 × 10 −1 [31] MWCNT/Nafion Mixing 0.75 [32] MWCNT-PDDA/MWCNT-DOC/PEDOT LbL + In situ polymerization 155 [16] www.advancedsciencenews.com © 2020 Wiley-VCH GmbH…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%